(untitled) (Global Journal of Science Frontier Research, 2021)
Weed interference decreases okra (Albelmoschus esculentus (L.)Moench) yields. Weeding is mostly manual with drudgery and cost, unlike the use of herbicides. Herbicides identified for okra productivity are few and scarce. Objectives of this experiment are to evaluate the tolerance and development of okra to three frequently used herbicides. But achlor, diuron and atrazine+alachlor, at 2.0, 3.6 and 3.3 kga.i./ha, respectively, were screened for weed control in okra. Hoe-Weeded (HWC) and un-weeded plots (WDC) served as controls. Data collected were subjected to statistical analysis. Okra establishment was in the order of 91.8% (HWC)> 89.0% (butachlor)> 86.8% (WDC)> 70.8% (atrazine+alachlor)> 51.9% (diuron). But achlor at 2.0kg a.i./ha was safe on okra. Diuron at 3.6kg a.i./ha was severely (7.8) phytotoxic, while atrazine+alachlor at 3.3kg a.i./ha was moderately (4.4) phytotoxic on okra, on 0-10 scale. Shoot biomass of 7.35g/plant in okra grown in butachlor treated plots were similar to 7.90g/plant in HWC, and greater than 1.4g/plant in diuron treated plots, 3.5 and 3.45g/plant in atrazine+alachlor and WDC, respectively. The herbicides had better weed control than WDC. Butachlor had no phytotoxic effect on okra and had okra establishment and shoot biomass comparable with HWC and should be listed for weed control in okra production.